Drug Release Profiles of Mitomycin C Encapsulated Quantum Dots-Chitosan Nanocarrier System for the Possible Treatment of Non-Muscle Invasive Bladder Cancer - Fariza Aina Abd Manan; Nor Azah Yusof; Jaafar Abdullah; Faruq Mohammad; Armania Nurdin; Latifah Saiful Yazan; Sachin K. Khiste; Hamad A. Al-Lohedan (MDPI AG, 2021)
Nanotechnology-based drug delivery systems are an emerging technology for the targeted delivery of chemotherapeutic agents in cancer therapy with low/no toxicity to the non-cancer cells. With that view, the present work reports the synthesis, characterization, and testing of Mn:ZnS quantum dots (QDs) conjugated chitosan (CS)-based nanocarrier system encapsulated with Mitomycin C (MMC) drug. This fabricated nanocarrier, MMC@CS-Mn:ZnS, has been tested thoroughly for the drug loading capacity, drug encapsulation efficiency, and release properties at a fixed wavelength (358 nm) using a UV-Vis spectrophotometer. Followed by the physicochemical characterization, the cumulative drug release profiling data of MMC@CS-Mn:ZnS nanocarrier (at pH of 6.5, 6.8, 7.2, and 7.5) were investigated to have the highest release of 56.48% at pH 6.8, followed by 50.22%, 30.88%, and 10.75% at pH 7.2, 6.5, and 7.5, respectively. Additionally, the drug release studies were fitted to five different pharmacokinetic models including pesudo-first-order, pseudo-second-order, Higuchi, Hixson-Crowell, and Korsmeyers-Peppas models. From the analysis, the cumulative MMC release suits the Higuchi model well, revealing the diffusion-controlled mechanism involving the correlation of cumulative drug release proportional to the function square root of time at equilibrium, with the correlation coefficient values (R2) of 0.9849, 0.9604, 0.9783, and 0.7989 for drug release at pH 6.5, 6.8, 7.2, and 7.5, respectively. Based on the overall results analysis, the formulated nanocarrier system of MMC synergistically envisages the efficient delivery of chemotherapeutic agents to the target cancerous sites, able to sustain it for a longer time, etc. Consequently, the developed nanocarrier system has the capacity to improve the drug loading efficacy in combating the reoccurrence and progression of cancer in non-muscle invasive bladder diseases.